Organic solvents enhance polyvinyl alcohol/polyethylene glycol self‐healing hydrogels for artificial cartilage. (15th July 2022) - Ye, Zishuo; Lu, Hailin; Jia, Endong; Chen, Jian; Fu, Lifeng
Abstract: Polyvinyl alcohol (PVA) hydrogels have potential applications in bionic articular cartilage due to their good biocompatibility and low friction. However, the lack of adequate mechanical properties is a key obstacle for PVA hydrogels to replace natural cartilage. In this study, polyethylene glycol (PEG) was introduced into the PVA hydrogel, and the (PVA/PEG) composite gels were prepared by a blending physical cross‐linking method. The PVA/PEG gels were treated with a simple and novel organic solvent immersion dehydration to improve its mechanical and tribological properties. And the using of organic solvents for dehydration changed the network structure of the PVA/PEG gels, which improved the mechanical properties effectively. In this study, the effects of different organic solvents on the tribological properties, swelling ratio, shore hardness, and dehydration rate of PVA/PEG hydrogels were investigated. Compared with natural drying, organic solvent dehydration reduced the gel formation time. Notably, the organic solvent dehydration treatment reduces the wear rate of PE ball friction pair to 27.4% of the original amount, improving wear resistance. Meanwhile, self‐healing and cellular immune assays demonstrated the excellent biocompatibility and self‐healing ability of the PVA/PEG gels. This study provides a new candidate material for the design of articular cartilage, which is expected to advance the progress of artificial cartilage repair.